Cushing's syndrome in the elderly: data from the European Registry on Cushing's syndrome. Issue 4 (7th February 2023) - Amodru, Vincent; Ferriere, Amandine; Tabarin, Antoine; Castinetti, Frederic; Tsagarakis, Stylianos; Toth, Miklos; Feelders, Richard A; Webb, Susan M; Reincke, Martin; Netea-Maier, Romana; Kastelan, Darko; Elenkova, Atanaska; et al.
Abstract: Objective: To evaluate whether age-related differences exist in clinical characteristics, diagnostic approach, and management strategies in patients with Cushing's syndrome (CS) included in the European Registry on Cushing's Syndrome (ERCUSYN). Design: Cohort study. Methods: We analyzed 1791 patients with CS, of whom 1234 (69%) had pituitary-dependent CS (PIT-CS), 450 (25%) adrenal-dependent CS (ADR-CS), and 107 (6%) had an ectopic source (ECT-CS). According to the WHO criteria, 1616 patients (90.2%) were classified as younger (<65 years old) and 175 (9.8%) as older (≥65 years old). Results: Older patients were more frequently males and had a lower Body Mass Index (BMI) and waist circumference when compared with the younger. Older patients also had a lower prevalence of skin alterations, depression, hair loss, hirsutism, and reduced libido, but a higher prevalence of muscle weakness, diabetes, hypertension, cardiovascular disease, venous thromboembolism, and bone fractures than younger patients, regardless of sex ( P < .01 for all comparisons). Measurement of urinary free cortisol supported the diagnosis of CS less frequently in older patients when compared with the younger ( P < .05). An extrasellar macroadenoma (macrocorticotropinoma with extrasellar extension) was more common in older PIT-CS patients than in the younger ( P < .01). Older PIT-CS patients more frequently received cortisol-lowering medications and radiotherapy as a first-line treatment, whereas surgery was the preferred approach in the younger ( P < .01 for all comparisons). When transsphenoidal surgery was performed, the remission rate was lower in the elderly when compared with their younger counterpart ( P < .05). Conclusions: Older CS patients lack several typical symptoms of hypercortisolism, present with more comorbidities regardless of sex, and are more often conservatively treated.